2012
DOI: 10.1590/s0103-64402012000100004
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity by DPPH assay of potential solutions to be applied on bleached teeth

Abstract: The aim of this study was to assess, using the DPPH assay, the antioxidant activity of several substances that could be proposed to immediately revert the problems caused by bleaching procedures. The percentage of antioxidant activity (AA%) of 10% ascorbic acid solution (AAcidS), 10% ascorbic acid gel (AAcidG), 10% sodium ascorbate solution (SodAsS), 10% sodium ascorbate gel (SodAsG), 10% sodium bicarbonate (Bicarb), Neutralize(®) (NE), Desensibilize(®) (DES), catalase C-40 at 10 mg/mL (CAT), 10% alcohol solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
160
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(200 citation statements)
references
References 20 publications
7
160
0
12
Order By: Relevance
“…10 Fractions obtained from both extracts showed potential antioxidant activity may due to the presence of higher amount of alkaloids, flavonoids and phenols based on qualitative phytochemical screening results. Medini et al (2014) reported that antioxidant capacity is highly associated with phenolic content and most of the radical scavenging activity of plants is derived from phenols.…”
Section: Discussionmentioning
confidence: 96%
“…10 Fractions obtained from both extracts showed potential antioxidant activity may due to the presence of higher amount of alkaloids, flavonoids and phenols based on qualitative phytochemical screening results. Medini et al (2014) reported that antioxidant capacity is highly associated with phenolic content and most of the radical scavenging activity of plants is derived from phenols.…”
Section: Discussionmentioning
confidence: 96%
“…DPPH free radical scavenging assay is the simplest method for evaluating the antioxidant potential of an extract [24] , which is based on the electron-transfer that produces a violet solution [25] . This free radical, stable at room temperature, is reduced in the presence of an antioxidant molecule, giving rise to a colourless solution [26] . With this method, the determination of antiradical power of an antioxidant is possible by measuring the decrease in absorbance of DPPH at 517 nm [27] .…”
Section: Resultsmentioning
confidence: 99%
“…13,14,[16][17][18] In a previous study, 10% ascorbic acid applied for only one minute was effective in increasing the bond strength of bleached teeth. 18 The ionized form of ascorbic acid, namely, sodium ascorbate, was tested in different concentrations and for different time periods, but a recent study 26 suggests that 10% sodium ascorbate was not effective in increasing the bond strength of composites to bleached enamel and/or dentin.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11] Recently, some attempts to reduce the immediate inability of adhesion have been made with antioxidant solutions applied to the tooth structure after bleaching procedures. Many antioxidant agents have been tested, such as sodium ascorbate, [12][13][14][15][16][17] ascorbic acid, 17,18 α-tocopherol 12,17 and even a solution of grape seed extract. 19 Their presentation varies from solutions to gels, and application time varies from ten minutes 19 to one hour.…”
Section: Introductionmentioning
confidence: 99%